Sosialisasi dan Pendampingan Pelaksanaan 5R Bagi Karyawan Golden Leaves Jaya Abadi Malang - Made Iska Aprilita Wardani; Tasnim Nikmatullah Realita (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Problems of productivity, inefficiency, inconsistency in production results are common problems faced by business actors. However, this should not be allowed to continue to occur because it will reduce business competitiveness. Make continuous improvement efforts using techniques that are adapted to the availability of resources. The 5S technique can be an option for business actors to carry out continuous improvements in accordance with the limited resources they have. This community service is intended to provide insight, strengthen knowledge and skills in implementing 5S for leaders and employees, especially at PT Golden Leaves Jaya Abadi (GLJA). This community service activity includes outreach, training and assistance in structuring office layouts and fabrication to facilitate the movement of goods, materials and people in offices and production areas. After carrying out this community service activity, you can feel an increase in efficiency that comes from the short time for the movement of materials, goods and people. Implementation of 5R is also felt to facilitate coordination between sections so that work effectiveness can be obtained.